The evolution of UAVs applications in urban planning - Mohd Noor, Norzailawati; Rusni, Nur Aulia (‘Coordinates Media Pvt. Ltd., 2017)
Remote sensing UAVs/drones applications have changed the people view on urban and city planning. The latest technologies on remotely-sensed applications allow people to see and understand their neighborhood from above. This paper attempts to review on the evolution of remote sensing UAVs/drones application from the urban planning perspectives. Thus, the objectives of the review include the trends and issues of UAVs/drones usage in the urban area, types, and functions of UAVs/drones in the urban planning context, as well as law and regulation concerning remote sensing UAVs/drones’ applications by international and local organizations. The methodology used includes literature reviews of paper articles, journals, books, website and official document related to UAVs/drones and urban planning. The findings and discussions are expected to help the professionals especially those who involve in urban planning field and encourage them to apply new and updated technological approach for smart and sustainable planning. Previous research proved that UAVs/drones have given remote sensing a new appeal for scientists, who will now be able to conduct studies in a much more flexible way and become the preferred platform for the development of remote sensing instruments and applications, especially in urban studies.